Warfare and belligerence : perspectives in First World War studies - Purseigle, Pierre (History of warfare ;, 2005)
This collection of essays suggests some of the ways in which an interdisciplinary perspective may contribute to our understanding of the First World War. Its contributors examine the relationship between the character of the war and the nature of belligerent societies, and present original research on the comparative history of the Great War.